Performance Analysis of Air-refrigeration System for Data Center Cooling - Sui Qiuyu; Ma Guoyuan; Liu Shuailing; Xu Shuxue; Ma Hongxia (Zhileng xuebao)
In this study, an air-refrigeration system for data center cooling is proposed. The effects of pressure ratio, ambient temperature, indoor temperature, and rotating component efficiencies (compressor and expander) on cycle performance were studied by numerical simulation. Approaches to improve the system performance are proposed, and the performance of the composite system comprising the air-refrigeration system and the free cooling system in typical climate cities is analyzed. The results show that the optimal pressure ratio is 1.5–2.0 in the actual air-refrigeration cycle. The unit refrigerationcapacity and refrigeration coefficient of performance (COP) increase with a decrease in ambient temperature or an increase in indoor temperature. The efficiency of the expander is more critical than that of the compressor for improving the performance of the air-refrigeration system. Under the optimal pressure ratio of the actual cycle (both rotating component efficiencies = 0.8), the refrigeration COP can be increased by 22% by implementingthe recuperator. The annual energy efficiency ratio (AEER) of the composite system in Hohhot can reach 14.61, indicating that it has more advantages in areas with a long freecooling period throughout the year.